Ransomware Attack Analysis in Cybersecurity - Stefanus Eko Prasetyo; Heru Wijayanto Aripradono; Ricardo (Politeknik Piksi Ganesha Indonesia, 2025)
Ransomware attacks have emerged as a significant threat to computer security in the digital age. This research aims to analyze ransomware attacks within the context of cybersecurity, specifically focusing on the impact of such attacks on an organization's database infrastructure. The study involves simulating ransomware attacks using techniques commonly employed by attackers in real-world scenarios. It includes a comprehensive literature review, case observations of previous ransomware attacks, and system simulations to understand the nature of these attacks and their potential consequences. The research highlights the need for effective mitigation strategies to safeguard critical organizational infrastructure and provide insights into strengthening defenses against ransomware. The findings of this study are expected to contribute to the development of more effective and sustainable cybersecurity strategies to address the growing complexity of cyber threats and ensure the operational continuity of organizations.Keywords: Ransomware attacks, Cybersecurity, Database infrastructure